Weighted boundedness for multilinear Littlewood-Paley and Marcinkiewicz operators on Morrey spaces - Liu Lanzhe (Հայաստանի ԳԱԱ)
Some sharp estimates for multilinear operators are used to prove weighted boundedness for the multilinear Littlewood-Paley and Marcinkiewicz operators on the Morrey spaces.
Keywords: Mathematics; Science